Safety and tolerability of guadecitabine (SGI-110) in patients with myelodysplastic syndrome and acute myeloid leukaemia: a multicentre, randomised, dose-escalation phase 1 study. Issue 9 (September 2015) - Issa, Jean-Pierre J; Roboz, Gail; Rizzieri, David; Jabbour, Elias; Stock, Wendy; O'Connell, Casey; Yee, Karen; Tibes, Raoul; Griffiths, Elizabeth A; Walsh, Katherine; Daver, Naval; Chung, Woonbok; et al.
Summary Background Hypomethylating agents are used to treat cancers driven by aberrant DNA methylation, but their short half-life might limit their activity, particularly in patients with less proliferative diseases. Guadecitabine (SGI-110) is a novel hypomethylating dinucleotide of decitabine and deoxyguanosine resistant to degradation by cytidine deaminase. We aimed to assess the safety and clinical activity of subcutaneously given guadecitabine in patients with acute myeloid leukaemia or myelodysplastic syndrome. Methods In this multicentre, open-label, phase 1 study, patients from nine North American medical centres with myelodysplastic syndrome or acute myeloid leukaemia that was refractory to or had relapsed after standard treatment were randomly assigned (1:1) to receive subcutaneous guadecitabine, either once-daily for 5 consecutive days (daily × 5), or once-weekly for 3 weeks, in a 28-day treatment cycle. Patients were stratified by disease. A 3 + 3 dose-escalation design was used in which we treated patients with guadecitabine doses of 3–125 mg/m2 in separate dose-escalation cohorts. A twice-weekly treatment schedule was added to the study after a protocol amendment. The primary objective was to assess safety and tolerability of guadecitabine, determine the maximum tolerated and biologically effective dose, and identify the recommended phase 2 dose of guadecitabine. Safety analyses included all patients who received at least one dose of guadecitabine. Pharmacokinetic and pharmacodynamic analyses to determine the biologically effective dose included all patients for whom samples were available. This study is registered with ClinicalTrials.gov, number NCT01261312. Findings Between Jan 4, 2011, and April 11, 2014, we enrolled and treated 93 patients: 35 patients with acute myeloid leukaemia and nine patients with myelodysplastic syndrome in the daily × 5 dose-escalation cohorts, 28 patients with acute myeloid leukaemia and six patients with myelodysplastic syndrome in the once-weekly dose-escalation cohorts, and 11 patients with acute myeloid leukaemia and four patients with myelodysplastic syndrome in the twice-weekly dose-escalation cohorts. The most common grade 3 or higher adverse events were febrile neutropenia (38 [41%] of 93 patients), pneumonia (27 [29%] of 93 patients), thrombocytopenia (23 [25%] of 93 patients), anaemia (23 [25%] of 93 patients), and sepsis (16 [17%] of 93 patients). The most common serious adverse events were febrile neutropenia (29 [31%] of 93 patients), pneumonia (26 [28%] of 93 patients), and sepsis (16 [17%] of 93 patients). Six of the 74 patients with acute myeloid leukaemia and six of the 19 patients with myelodysplastic syndrome had a clinical response to treatment. Two dose-limiting toxicities were noted in patients with myelodysplastic syndrome at 125 mg/m2 daily × 5, thus the maximum tolerated dose in patients with myelodysplastic syndrome was 90 mg/m2 daily × 5. The maximum tolerated dose was not reached in patients with acute myeloid leukaemia. Potent dose-related DNA demethylation occurred on the daily × 5 regimen, reaching a plateau at 60 mg/m2 (designated as the biologically effective dose). Interpretation Guadecitabine given subcutaneously at 60 mg/m2 daily × 5 is well tolerated and is clinically and biologically active in patients with myelodysplastic syndrome and acute myeloid leukaemia. Guadecitabine 60 mg/m2 daily × 5 is the recommended phase 2 dose, and these findings warrant further phase 2 studies. Funding Astex Pharmaceuticals, Stand Up To Cancer.